2014
DOI: 10.1094/mpmi-07-13-0187-fi
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Type III Secretion Assay for Delivery of Fungal Effector Proteins into Wheat

Abstract: Large numbers of candidate effectors from fungal pathogens are being identified through whole-genome sequencing and in planta expression studies. Although Agrobacterium-mediated transient expression has enabled high-throughput functional analysis of effectors in dicot plants, this assay is not effective in cereal leaves. Here, we show that a nonpathogenic Pseudomonas fluorescens engineered to express the type III secretion system (T3SS) of P. syringae and the wheat pathogen Xanthomonas translucens can deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 54 publications
0
93
0
1
Order By: Relevance
“…For this, the promoter of the P. syringae effector gene AvrRpm1 (Upadhyaya et al, 2014) followed by a Gateway cassette, sfGFP11, HA epitope tag, and AvrRpm1 terminator was introduced into the broad-host-range vectors pBBR1MCS-2 and -5 (Kovach et al, 1995) ( Figure 4B). To deliver effectors from other pathogens that do not use T3SS, we engineered vectors with the AvrRpm1 promoter followed by a T3SS signal peptide (Upadhyaya et al, 2014). Since a very small amount of the effectors might be delivered from bacteria, we generated vectors containing 2xsfGFP11 to improve the fluorescence signal ( Figure 4B).…”
Section: Development Of Sfgfp11 Tag System For Live Cell Imaging Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, the promoter of the P. syringae effector gene AvrRpm1 (Upadhyaya et al, 2014) followed by a Gateway cassette, sfGFP11, HA epitope tag, and AvrRpm1 terminator was introduced into the broad-host-range vectors pBBR1MCS-2 and -5 (Kovach et al, 1995) ( Figure 4B). To deliver effectors from other pathogens that do not use T3SS, we engineered vectors with the AvrRpm1 promoter followed by a T3SS signal peptide (Upadhyaya et al, 2014). Since a very small amount of the effectors might be delivered from bacteria, we generated vectors containing 2xsfGFP11 to improve the fluorescence signal ( Figure 4B).…”
Section: Development Of Sfgfp11 Tag System For Live Cell Imaging Of Pmentioning
confidence: 99%
“…For the expression vector of the bacterial T3E with sfGFP11, broadhost-range vector, pBBR1MCS-2 and -5 (Kovach et al, 1995) were modified to introduce AvrRpm1 promoter (Upadhyaya et al, 2014) followed by the Gateway cassette with AvrRpm1 terminator. The series of sfGFP11 and linker were amplified using synthetic oligos and the corresponding fragments were introduced after the Gateway cassette in frame (Supplemental Figure 1B).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Pseudomonas spp. have been used as a delivery vehicle in Arabidopsis thaliana to characterize oomycete effector proteins by fusion to the type III signals of avirulence proteins AvrRps4 and AvrRpm1 (Rentel et al 2008;Sohn et al 2007); this system was also recently used in wheat to investigate effector candidates from the stem rust fungus Puccinia graminis tritici (Upadhyaya et al 2014). Additionally, Sharma and colleagues (2013) have employed the Burkholderia glumae T3S system to transfer Magnaporthe oryzae effectors to rice cells.…”
Section: Bsmv-vigs Of Bec1019 Impedes Fungal Growth In Incompatible Imentioning
confidence: 99%
“…viciaefabae [90] , and PGTAUSPE-10-1 in the wheat stem rust fungus Pgt [91] . All of these proteins are thought to be translocated from haustoria to the host cell.…”
Section: Secretomementioning
confidence: 99%
“…Immunocytological and biochemical studies indicated that RTP1 is a member of a new class of structural effectors, which are capable of forming filamentous structures in vitro and in vivo [93] . Due to the induction of cell death in the host line carrying the resistance gene Sr22, PGTAUSPE-10-1 was considered as a candidate AvrSr22 [91] . Apart from the six rust effectors, only a few secreted proteins have been cloned as candidate effectors on the basis of expressed sequence tags and cDNA library from Pst.…”
Section: Secretomementioning
confidence: 99%